ACCOUNTABILITY OF INFLUENCERS WHO CREATE ONLINE GAMBLING PROMOTIONAL CONTENT ON INSTAGRAM - Muhammad Abdillah Novaliando; Zeehan Fuad Attamimi (LPPM, Universitas Muhammadiyah Riau, 2024)
The prevalence of online gambling and internet media in the community is one of the negative effects. It is impossible to separate the role influencers play in promoting online gambling sites from the evolution of online gaming. In spite of the fact that it is expressly forbidden to promote online gambling in Law No. 19 of 2016 concerning Electronic Information and Transactions and its amendments (particularly in Article 27 paragraph (2) and Article 45 paragraph (2)). This research aims to ascertain the extent of influencers' responsibility for endorsing online gambling as well as their participation in its promotion. The normative juridical approach is the research methodology used. According to the study's findings, influencers may play a more active role in the marketing of online gambling than merely acting as a promotional party. Influencers may take on the roles of uitlokker, medeplichig, plegen, doen plegen, or medeplegen. Influencer. An influencer must also be responsible for the content they promote. If the content is not in line with the rules, the influencer may receive penalties that can be based on Instagram's terms of use such as account termination or even deletion and based on laws such as imprisonment and fines.